Datos históricos relevantes de la División Geología del Museo de La Plata: desde Rodolfo Hauthal hasta Alfredo J. Cuerda - Cingolani, Carlos Alberto (2013)
The history of the Geology Division of the La Plata Museum started with Francisco P Moreno who was the first to dedicate a showroom to Geology and Mineralogy, Later, he was the leader of several expeditions to Patagonia and in 1891 he was in charge to designate the German geologist Rodolfo (Rudolf) Hauthal as the first chief of the ‘Geological Section’, who spent 14 years working at the Museum. Hauthal provided important geological contributions on different areas of Argentina and also with Moreno was part of the Argentine-Chilean Limits Commission. The documentation left by Rodolfo Hauthal includes several papers; many of them published in the Revista del Museo de La Plata. The paleontological discoveries of Hauthal and co-authors in the caves of Ultima Esperanza had a special impact. After his return to Germany, he was replaced by another German geologist invited by Moreno: Walther Schiller. He worked in the Museum of La Plata for 40 years, interrupted only by the time he returned to Germany to participate in World War I. The performance of Schiller, who settled down in La Plata with his family, was a long lasting legacy for the Geology of the Museum. He died during an expedition to the Aconcagua in 1944. The Museum belonged to the Province of Buenos Aires until 1905, when it was incorporated as a part of the new National University of La Plata after the resignation of its Director E P. Moreno. In 1920 the Museum was reorganized into five different Departments: Anthropology, Geology and Mineralogy, Vertebrate Paleontology, Invertebrate Paleontology and Zoology. In 1923, a new re-organization was approved; Schiller occupied the Geology and Physical Geography and the Mineralogy and Petrography Departments. At this time Juan Keidel was incorporated in the geological staff of the Museum as a Visitor Professor. Then Angel V. Borrello, graduated from the Institute of Museum” became the new Chief of the Geological Division. He made relevant institutional contributions, recognized the importance of magmatism in geological evolution processes and founded the first laboratory of Rb-Sr geochronology in the Department of Geology from the Scientific Commission of the Buenos Aires province that also interacted constantly with the Geology Division of the Museum. The permanent public concern for the published and unpublished literature in the country, led him to make agreements with the Secretaria de Mineria de la Nación, in this way, more than 12,000 bibliography references were preserved in the Geology Division. In 1958 Alfredo J. Cuerda was incorporated as Associate Professor of Historical Geology. Later in 1971, he replaced A. V. Borrello after his death and served as a Chief of Geology Division until 1998. In the 1960 A, Cuerda began an activity that would become his true passion: the study of graptolites. Fe produced several syntheses af Ordovician Systems, Silurian-Devonian and many hiostratigraphical papers. Lt is important to note that several South American studied specimens are a valuable scientific heritage. In the late 1970s different geological research groups from Geology Division and athers working in the Museum discuss to create a new institution: a Geological Research Centre (CIG).